2018
DOI: 10.1016/j.mvr.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal mechanical trauma alters the electrochemical properties and increases aggregation of erythrocytes

Abstract: Circulation of blood depends, in part, on the ability of red blood cells (RBCs) to aggregate, disaggregate, and deform. The primary intrinsic disaggregating force of RBCs is derived from their electronegativity, which is largely determined by sialylated glycoproteins on the plasma membrane. Given supraphysiological shear exposure - even at levels below those which induce hemolysis - alters cell morphology, we hypothesized that exposure to supraphysiological and subhemolytic shear would cleave membrane-bound si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…When standardizing for hematocrit, the intrinsic physical properties of RBCs—that is, cellular deformability and their tendency to form reversible multi‐cell aggregates—govern blood fluidity. Previous experimentation has established that exposure to supraphysiological shear environments may cause both increased RBC aggregation and decreased RBC deformability in human blood samples 47,48 . Normal bovine RBC do not readily form aggregates; however, have been shown to aggregate following exposure to a centrifugal blood pump in vivo 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When standardizing for hematocrit, the intrinsic physical properties of RBCs—that is, cellular deformability and their tendency to form reversible multi‐cell aggregates—govern blood fluidity. Previous experimentation has established that exposure to supraphysiological shear environments may cause both increased RBC aggregation and decreased RBC deformability in human blood samples 47,48 . Normal bovine RBC do not readily form aggregates; however, have been shown to aggregate following exposure to a centrifugal blood pump in vivo 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimentation has established that exposure to supraphysiological shear environments may cause both increased RBC aggregation and decreased RBC deformability in human blood samples. 47,48 Normal bovine RBC do not readily form aggregates; however, have been shown to aggregate following exposure to a centrifugal blood pump in vivo. 48 Further exploration of underlying RBC alterations following exposure to high mechanical shear stresses could reveal sublethal-specific alterations and potentially identify new markers sensitive to detecting pre-hemolytic blood trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of blood to supraphysiological shear stresses, below hemolytic levels at which cell rupture is induced, alters the physical and electrochemical properties of RBCs by remodeling the membrane, denaturing cytoskeletal proteins, and thinning the glycocalyx 18,27‐29 . A number of recent reports have identified that exposure of RBCs to sublethal mechanical trauma also decreases RBC deformability as measured using laser diffractometry 13,16,17,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Within circulation, the physiological shear stresses that RBCs are exposed to typically range from 0‐10 Pa 12 Mechanical stresses >10 Pa therefore represent a supraphysiological condition; initially, cells tolerate these stresses without substantial effects, although biophysical properties of cells become impaired when exposed to 40‐80 Pa (depending on exposure duration 13 ) and eventually hemolyze at shears >150 Pa (again, depending on exposure duration 12,14,15 ). The range of shears that induce biophysical impairment to RBC are progressively termed “sublethal,” while stresses that induce overt cell destruction are hemolytic and/or “lethal.” Recent advances in characterizing mechanically induced blood damage identified that shear stress magnitudes that are supraphysiological, yet non‐lethal, can negatively impact RBC structure and function as evidenced through: (a) aberrations to cell morphology 16 ; (b) decreased cellular deformability 17 ; (c) altered cell electronegativity and cell surface chemistry and thus thresholds for cell aggregation/disaggregation 18 ; and (d) cell fragmentation 19 . The extent to which these alterations influence in vivo hemodynamics remains to be elucidated, although it is hypothesized that altered RBC mechanobiology may propagate malperfusion and/or flow stagnation that lead to poor tissue oxygenation 11,20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation